A SYNTHESIS OF EMOTIONAL QUOTIENT IN DEALER MANAGEMENT IN THE ELECTRIC CAR DISTRIBUTION CHANNEL IN BANGALORE - Basava Aradhya, Dr. Guru; Gowda KJ, Mr Madan; Majumder, Ms. Deblina; Gurao, Mr Kamesh (The journal of contemporary issues in business and government, 2022)
The replacement of fossil fuel-based cars by an electric one is of paramount interest to car companies. The major challenges associated with it are not only building the required infrastructure but also educating and supporting the consumers to endure this mammoth change. The breakthrough in areas like the driving range of the electric engine, their price point, use of clean energy to manufacture batteries will decide the fate of this endeavor in near future. In this regard, the car dealers can play a very important role to educate and support the customers to adopt this change. In this project, we have collected feedback from 77 electric car dealers of Bengaluru, regarding the emotional quotient in dealer management. The primary goal of this research is to examine customer perceptions and purchase intentions for electric automobiles in Bengaluru, as well as how the customer-dealership connection influences the purchasing process. This study shows that customers are ready to make this transition and the respective car dealer are also doing their part to make this journey a smooth one, also shows us as a customer, what features a dealer need to add to the dealership business to build a pleasant a dealer- customer relationship.